2009
DOI: 10.1055/s-0029-1241859
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Lipid Transporters ABCA3 and ABCA1 is Diminished in Human Breast Cancer Tissue

Abstract: ATP-binding cassette transporters ABCA3 and ABCA1 are related to a differentiated, lipid-secreting phenotype of type II pneumocytes. Since mammary gland epithelial cells also show pronounced lipid metabolism and secretion, we investigated the expression of these proteins in normal as well as in neoplastic breast tissue. Normal human breast tissue, breast cancer cell lines, and 162 tumor samples of patients with primary unilateral invasive breast cancer were analyzed for ABCA3 and ABCA1 protein expression by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 19 publications
4
46
0
Order By: Relevance
“…All statistical comparisons are to the corresponding "scr" exposure control. mediated death in cancer cells by increasing mitochondrial cholesterol (41), and it has been proposed that this finding could underlie other recent reports linking ABCA1 deficiency to cancer (42,43). Given this, some of the targets we found increased in Abca1 Ϫ/Ϫ DRMs may possibly underlie the cancer cell survival advantage recently associated with ABCA1 deficiency.…”
Section: Discussionsupporting
confidence: 79%
“…All statistical comparisons are to the corresponding "scr" exposure control. mediated death in cancer cells by increasing mitochondrial cholesterol (41), and it has been proposed that this finding could underlie other recent reports linking ABCA1 deficiency to cancer (42,43). Given this, some of the targets we found increased in Abca1 Ϫ/Ϫ DRMs may possibly underlie the cancer cell survival advantage recently associated with ABCA1 deficiency.…”
Section: Discussionsupporting
confidence: 79%
“…The data shown in Figure 8.3 and those published by others (Schimanski et al, 2009) suggest a physiological role for ABCA1 in the lactating mammary gland. Furthermore they may suggest that ABCG1 could be more important for processes occurring in mammary secretory cells of lactating rather than nonlactating mammary tissue.…”
supporting
confidence: 70%
“…ABCA1 and ABCA3 expression was identified by immunohistochemistry in the epithelium of normal as well as in neoplastic human breast tissues, but also in breast cancer cell lines (Schimanski et al, 2009). It was reported that ABCA3 and ABCA1 were highly expressed in normal mammary gland epithelium.…”
Section: Protein Localization Of Cholesterol Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…ABCA3 expression in lung cancer appears to be closely associated with adenoid differentiation, an observation recently also made in breast cancer. In mammary cancer tissue, the level of ABCA3 expression correlated with the degree of glandular differentiation, and lower levels of ABCA3 expression were associated with a more aggressive phenotype of the tumor cells [29]. This appears similar to the situation in lung cancer with low expression levels of ABCA3 in SCLC, the most aggressive variant of the disease.…”
Section: Discussionmentioning
confidence: 87%